Re-design Interior Petground Kenjeran Surabaya dengan Pendekatan Green Design - Cindy Tan Antandi Putri (Intra, 2017)
In modern era, dogs have been popular among people of all ages. Begins to emerge community of dog lovers, where many of the lovers or dog owners who want to provide and meet various facilities to pamper and care dogs. There are no many dog lovers who socialize and brainstorm about dog care and training. Fact, there is no place provide complete facilities for dog lovers in Surabaya. Kenjeran Petground is one of the place for dog lovers to provide facilities for dogs. The concept design is provide facilities for dogs and owners in one location with natural atmosphere formed in the design as reflection of the nature and character of the dog. Through the method of design thinking by paying attention to the dog needs and dog lovers needs, so the petground is designed using green design approach. Green design approach is applied to this design with LED lamp for energy efficency , material and finishing low-impact. From the green design will be get stability, both for hygiene and health in the room.